Gross Motor Skills Review of Elementary School Children 127 Pekanbaru - Apriani, Leni; Alpen, Joni; Qomariah, Triatmini; Triputri, Vanny Hanema (STKIP Paasundan Press, 2025)
Gross Motor Skills is skills the movement that must be owned from an early age to support quality motion individual on life everyday. Purpose This research is For see the gross motor review of children. The research method used is quantitative descriptive with survey method. The population is SDN 127 Pekanbaru with sample class 1, 2, And 3 Which chosen in a way purposive sample amount to 47 students. The research instrument used the TGMD-2 test with data analysis looking for percentages. As for results his research show that 16% of students own ability very high motor skills, 8% high, 32% medium, 36% low, and 8% very low. This means that gross motor skills child Still classified as low and necessary improved.